WELL BEING PADA MAHASISWA AKHIR BERSUKU JAWA, SUNDA DAN BATAK DI KOTA SALATIGA - Ulil Irsyadiyah, Auliya (Jurnal Ilmu Psikologi dan Kesehatan (SIKONTAN), 2023)
Indonesia is a country with rich cultural diversity, including Javanese, Sundanese, and Batak tribes. Each tribe has different cultural characteristics, traditions, and values. In an academic context, it is important to understand how these cultural factors can affect the well-being of final students. Student well-being is an important factor in achieving academic and personal success. Understanding the level of well-being in final Javanese, Sundanese, and Batak students can help identify areas of concern in providing appropriate support and resources to improve their well-being. The purpose of this study is to determine the Overview of the Level of Well being in Final Students of Javanese, Sundanese, and Batak tribes in Salatiga City along with the influencing factors. The method used in this study is qualitative method with descriptive approach. The results of the study showed that Javanese, Sundanese, and Batak final students in Salatiga City experienced different well-being experiences based on factors such as cultural identity, social environment, and academic experience. Factors that influence well-being include: (1) Cultural identity; (2) Social support from family, peers, and tribal communities; (3) A supportive environment; (4) Stress factors; and (5) Balance between academic life and personal life.